2021
DOI: 10.1038/s41419-021-03452-x
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of ferroptosis in kidney tubular cell death under diabetic conditions

Abstract: Kidney tubular cell death induced by transforming growth factor-β1 (TGF-β1) is known to contribute to diabetic nephropathy, a major complication of diabetes. Caspase-3-dependent apoptosis and caspase-1-dependent pyroptosis are also involved in tubular cell death under diabetic conditions. Recently, ferroptosis, an atypical form of iron-dependent cell death, was reported to cause kidney disease, including acute kidney injury. Ferroptosis is primed by lipid peroxide accumulation through the cystine/glutamate ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(155 citation statements)
references
References 62 publications
3
123
0
1
Order By: Relevance
“…Herein, we proposed that the levels of iron and ferroptosis activity were signi cantly elevated in the spinal cord, which promoted tactile allodynia in DM rats. Similar results were obtained for other DM complications, such as diabetic nephropathy (Kim et al, 2021) and cardiomyopathy (Chen et al, 2020a), which indicated that the elevation of iron levels as well as the induction of cell ferroptosis in target organs was closely involved in the occurrence of DM complications.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Herein, we proposed that the levels of iron and ferroptosis activity were signi cantly elevated in the spinal cord, which promoted tactile allodynia in DM rats. Similar results were obtained for other DM complications, such as diabetic nephropathy (Kim et al, 2021) and cardiomyopathy (Chen et al, 2020a), which indicated that the elevation of iron levels as well as the induction of cell ferroptosis in target organs was closely involved in the occurrence of DM complications.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have indicated that the development of neuropathic pain secondary to peripheral nerve trauma appeared to occur alongside ferroptosis in the spinal dorsal horn neurons (Guo et al, 2021;Wang et al, 2021). Importantly, accumulating evidence has highlighted the role of iron-dependent ferroptosis in DM as well as a variety of diabetic complications, and the application of ferroptosis antagonists, including liproxstatin-1 (Lip-1) and ferrostatin-1 (Fer-1), demonstrated obvious curative effects against these hyperglycemia-induced complications (Kim et al, 2021;Li et al, 2020;Ma et al, 2020). Moreover, it was reported that a high glucose concentration results in DNP hypersensitivity, probably by disrupting the functions of cell mitochondria and subsequent generation of reactive oxygen species (ROS) (Sasson, 2017;Shokrzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 28 GPX4 overexpression inhibits ROS production and lipid peroxidation, 29 while a decrease in GPX4 activity or expression results in the accumulation of intracellular lipid peroxide, which leads to ferroptosis. 34 Recent studies have shown that knockout of GPX4 can activate macrophages and microglia in the kidney and hippocampus, trigger an inflammatory response, and ultimately lead to organ damage. 35 Interleukin-4 (IL)-4 and IL-13 can inhibit GPX4 expression, which coincides with increased expression of arachidonic acid lipoxygenases 15 (ALOX15) in a variety of tissues, such as lung, thus permitting robust production of key inflammatory intermediates.…”
Section: Mechanisms Of Ferroptosismentioning
confidence: 99%
“…Other researchers have also found ferroptosis-specific mitochondrial changes in the HK-2 cell line induced by high glucose, while fenofibrate regulates the ferroptosis signaling pathway to alleviate tissue damage [ 143 ]. In a recent study, typical features of ferroptosis were observed in kidney biopsy specimens of patients with DN [ 144 ]. This breakthrough will improve research on ferroptosis and DN, and studies will no longer be limited to the cellular and animal levels.…”
Section: Ferroptosis and Ckdmentioning
confidence: 99%